Cesium Lead Halide Nanocrystals based Flexible X‐Ray Imaging Screen and Visible Dose Rate Indication on Paper Substrate. Issue 8 (26th February 2022) - Chen, Huanyu; Wang, Qian; Peng, Guoqiang; Wang, Shuo; Lei, Yutian; Wang, Haoxu; Yang, Zhou; Sun, Jie; Li, Nan; Zhao, Lei; Lan, Wei; Jin, Zhiwen
Abstract: Metal halide semiconductors have huge potential on X‐ray detection, due to their high atomic number, adjustable photoluminescence wavelength, superior stability, and simple fabrication process. Here, cesium lead halide nanocrystals (CsPbX3 NCs) are fabricated on paper substrate as scintillator screen for the first time. By means of all‐solution processed spray‐coating method with optimization of polymethyl methacrylate, large‐area (>600 cm 2 ) and low‐cost (0.0975 dollar cm −2 ) flexible scintillator screens are obtained with high resolution (≈5 lp mm −1 ), low detection limit (2.97 μGy s −1 ), high light yield (≈30000 photons/MeV), and fast response speed (<15 ms). The screen can achieve high‐resolution X‐ray non‐distortion imaging for non‐planar objects and realize battery check and safety monitoring at a broad range of photon energy (10–160 keV). In addition, real‐time dose rates can be easily estimated through counting the luminous arcs of the designed visible indicator. More important, the screen shows remarkable tolerance to high‐dose X‐ray radiation (tolerance over 60 Gyair continuous radiation with only 3% performance degradation), water soaking (2000 h), and conventional storage (over 300 days without apparent deterioration under ambient conditions). Hence, this work may provide huge potential in the field of medical diagnosis, non‐planar detection, and safety monitoring in the future. Abstract : This work develops a universal strategy to obtain large area (>600 cm 2 ) X‐ray imaging with visible dose rate indication based on CsPbX3 nanocrystals on paper substrate. Such design endows the screen a flexible feature, tunable radioluminescence ability, and robust nature under various conditions (>60 Gyair continuous radiation, 2000 h water soaking, and >300 days ambient storage).